Forging partnerships among water and wastewater operators. (Metro Manila, Philippines Asian Development Bank, 2017)
Providing access to clean water continues to be a challenge for governments. To date, at least 1.8 billion people use drinking water sources that are contaminated and an estimated 663 million people across the globe do not have access to improved drinking water sources.The selected case briefs in this report provide an insight on the various partnerships created to improve local water utility operations and service delivery provision. Find out how peer-to-peer learning and mentoring can be used to spread expertise and best practices in the field of water utility operations to further improve sustainable water and wastewater service delivery.
Keywords: Sewage disposal -- Economic aspects -- Asia; Private sector development; Electronic books